Museum game-based learning: innovative approaches from a constructivist perspective - Li, Hui; Zhang, Muzhi (Frontiers in Education, 2025)
Constructivist learning theory emphasizes the subjectivity, sociality, and contextuality of learning, promoting learning through the creation of problem situations and guiding learners to collaborate and interact. Museums conduct educational activities for visitors through exhibits composed of physical objects and other supplementary forms. This paper proposes a model that integrates constructivist learning with game-based learning design, exploring the intrinsic mechanisms and implementation paths of game-based learning in museums to enhance the promotion of cultural heritage. Based on a hypothetical game scenario and analysis of museum game design practices, the paper discusses museum game design schemes grounded in constructivist principles, delves into the design methods of game-based learning in museums, and clarifies the pathways for embedding game elements and mechanisms into the use of cultural heritage resources. Through the analysis of the hypothetical game and established museum game design practices, this study demonstrates that museum game-based learning offers an effective approach to enhancing visitor engagement and learning. The application of the proposed constructivist GBL framework reveals how its six dimensions: self-determination, contextualization, social interaction, knowledge construction, meaning-making, and immediate feedback are reflected in actual implementations to varying degrees. The results of the analysis indicate that constructivist game-based learning holds strong potential for enhancing museum education. It is recommended that museums consider using a game-based learning model to design educational activities and exhibitions. To strengthen its applicability, future work could integrate inclusive design, ethical reflection, and longitudinal strategies. These efforts will help museums create more adaptive, inclusive, and sustainable learning experiences.